Does medical or surgical treatment for aortic stenosis improve outcome in dogs? - Thomas, Julia; Marshall, Sophie; Gormley, Karin; Conway, Georgia; Borgeat, Kieran (Veterinary Evidence, 2021)
PICO question In adult dogs with aortic stenosis does treatment with beta blockers compared with surgical intervention show a longer survival time with improved clinical parameters? Clinical bottom line Category of research question Treatment The number and type of study designs reviewed Eight studies were reviewed. One was a randomised controlled study, three were cohort studies, one was a case series and three were case reports Strength of evidence Moderate to weak Outcomes reported Intervention appeared to improve survival times ± physiological parameters when compared to no treatment at all. The severity of clinical signs was reduced, but the risk of sudden cardiac-related death was not diminished according to a number of papers. The direct comparison of surgical treatment with the use of beta blockers showed no significant difference in survival times or physiological parameters across all papers. There is not enough evidence available comparing the different beta blockers used for treatment to draw a meaningful conclusion as to which is more effective Conclusion Treatment of some form should be given to a dog diagnosed with aortic stenosis. This will improve clinical signs and there is evidence to say that it will prolong survival as well as improve quality of life. More research into this area is essential. Controlled, randomised clinical trials should be carried out in order to find a reliable and strong recommendation for treatment. Ethical implications need to be considered when going forward with this, which is why the evidence pool is likely to be so limited currently How to apply this evidence in practice The application of evidence into practice should take into account multiple factors, not limited to: individual clinical expertise, patient’s circumstances and owners’ values, country, location or clinic where you work, the individual case in front of you, the availability of therapies and resources. Knowledge Summaries are a resource to help reinforce or inform decision making. They do not override the responsibility or judgement of the practitioner to do what is best for the animal in their care.